Optimizing the use of the avoskin tiktok application and content attraction to buying interest - Situmeang, Ilona VO; Purwatiningsih, Sri Desti (Bricolage : Jurnal Magister Ilmu Komunikasi, 2025)
The rise of TikTok as a digital marketing platform has transformed consumer engagement in the skincare industry, particularly in promoting local brands like Avoskin to introduce his product to followers. This study investigates the influence of TikTok usage and content attractiveness on the buying interest of followers of the avoskinbeauty account. This research uses two theories media ecology theory and elaboration likelihood theory, the research explores the relationship between media usage, content engagement, and consumer behaviour. Adopting a positivist paradigm with a quantitative and explanatory approach, the study employed a survey method with 100 respondents selected using the Slovin formula, alongside 30 pretest participants. The results reveal a strong correlation (r = 0.783) between the use of the TikTok application and content attractiveness in shaping purchase interest. Hypothesis testing confirms a significant positive influence of both variables on the buying decisions of @avoskinbeauty followers. These findings highlight the strategic role of engaging content and platform utilisation in driving consumer behaviour in the digital era. theory of media ecology, studying how media technology affects society and its users. Aplication Tik Tok affects its users through what is presented in the advertisement in the application TikTok. The more interesting the content presented the more followers will be aware of the existence of Avoskin products and be interested the product. Elaboration likelihood theory, the central route can have an influence on the audience when they see the quality of information that they feel is high so that the audience can increase trust in the brand. Peripheral route is a route that occurs when the motivation possessed by the audience is less and the attitude evoked is determined by the positive or negative cues in the persuasive message can provide such strength; therefore, visualisation is important to attract the attention of audiences who have low motivation or are in the peripheral route.